Comparative energy content and amino acid digestibility of barley obtained from diverse sources fed to growing pigs - Hong Liang Wang; Meng Shi; Xiao Xu; Xiao Kang Ma; Ling Liu; Xiang Shu Piao (Asian-Australasian Journal of Animal Sciences, 2017)
Objective Two experiments were conducted to determine the content of digestible energy (DE) and metabolizable energy (ME) as well as the apparent ileal digestibility (AID) and standardized ileal digestibility (SID) of crude protein (CP) and amino acids (AA) in barley grains obtained from Australia, France or Canada. Methods In Exp. 1, 18 growing barrows (Duroc×Landrace×Yorkshire; 31.5±3.2 kg) were individually placed in stainless-steel metabolism crates (1.4×0.7×0.6 m) and randomly allotted to 1 of 3 test diets. In Exp. 2, eight crossbred pigs (30.9±1.8 kg) were allotted to a replicate 3×4 Youden Square designed experiment with three periods and four diets. Two pigs received each diet during each test period. The diets included one nitrogen-free diet and three test diets. Results The relative amounts of gross energy (GE), CP, and all AA in the Canadian barley were higher than those in Australian and French barley while higher concentrations of neutral detergent fiber, acid detergent fiber, total dietary fiber, insoluble dietary fiber and β-glucan as well as lower concentrations of GE and ether extract were observed in the French barley compared with the other two barley sources. The DE and ME as well as the SID of histidine, isoleucine, leucine and phenylalanine in Canadian barley were higher (p<0.05) than those in French barley but did not differ from Australian barley. Conclusion Differences in the chemical composition, energy content and the SID and AID of AA were observed among barley sources obtained from three countries. The feeding value of barley from Canada and Australia was superior to barley obtained from France which is important information in developing feeding systems for growing pigs where imported grains are used.